Animal-sourced model of human norovirus infection predicted using environmental DNA metabarcoding analysis - Yukuto Sato; Jun Yasuda; Masahiro Sakurai (Journal of Freshwater Ecology)
Human noroviruses (HNVs) are one of the major causes of food poisoning and severe gastroenteritis. However, prevention and medical treatment of HNV disease is underdeveloped due to the lack of ecological understanding of the HNVs including their host organisms. We address the potential source animals of HNVs based on the environmental DNA metabarcoding analysis. By focusing on the HNV-epidemic area in Japan, we found several bird species of ducks, pochards, carrion crow, and swan showing significant cross-correlation with the HNV detection from cultured oysters. Humans and livestock mammals do not exhibit correlation with HNVs. These results suggest an avian-sourced, non-human- or sewage-mediated model of HNV infection. Unraveling the unknown host animals of pathogens like HNV facilitates artificial propagation of the pathogen, leading to vaccine and small molecule drug development.